Thermodynamic Analysis of a Kalina Cycle Powered by Low-temperature Heat Source - Nguyen, Văn Dũng; Doan, Thị Hồng Hải; Nguyen, Văn Hạp; Tran, Văn Hưng; Nguyen, Minh Phú (Journal of Technical Education Science, 2022)
The Kalina cycle is a heat engine using an ammonia-water fluid pair. Therefore, the cycle can use a low-temperature heat source to generate mechanical energy. In this paper, a mathematical model for the Kalina cycle is formed and solved in EES software to evaluate the power and exergy destruction of each component in the cycle. From there the thermal efficiency and the exergy performance are appraised. The thermodynamic and flow parameters in each state are compared with published data to determine the accuracy of the mathematical model and the solution method. The analysis results show that a low temperature source of 110°C can provide heat for the Kalina cycle and achieve a thermal efficiency of nearly 13%. The exergy efficiency reaches up to 60% in the range considered. Exergy destruction of the condenser is the greatest. Therefore, further research is needed to improve the irreversibility of the condenser.